Varieties of Southern Religious Experiences - Hill, Samuel S. (Book collections on Project MUSE., 1988)
Varieties of Southern Religious Experience reflects the central assumption that there has been a distinct South for a long time, and effectively and engagingly examines the genuine diversity of that region's religious history.